REPRESENTASI MAKNA KASIH SAYANG AYAH DALAM FILM SEJUTA SAYANG UNTUKNYA - Sari, Rismaya Meuthia (SCIENTIA JOURNAL, 2023)
Film is a work of art that is produced based on the principle of cinematography and is an auditory communication tool that conveys messages to the audience, be it advice, education, entertainment, and information, by using symbolic forms that exist in humans in the form of messages, dialogue, and body movement. Film can produce various events in people’s daily lives, family life, friendship, love history, and so on. Rach film has a different way of packaging and presenting events or themes that will be assembled into a story based on the ideas converyed by the filmmaker. The film Sejuta Sayang Untuknya, which was released in 2020, tells the story of a single father named Actor Sagala who has to play a double role as a single parent who cares for and support the life of his only daughter, Gina after his wife dies. Working hard to pay for his daughter’s scholling in the midst of a family economic crisis. This study uses Rolland Barthes’s theory which is used to analyze the meaning and signs of affection shown by fathers towards their daughters. The purpose of this research is to understand the expression of a father’s affection for this daughter in life in the film Sejuta Sayang Untuknya.The method used in this study is a qualitative approach with Rolland Barthes semiotic analysis. The data collection technique used in this study was by observing the meaning and signs of a father’s affection obtained from the scenes, the dialogues of each character and analyzing the appearance. Keywords: Representations, Father’s Love, Semiotics, Rolland Barthes